Psychological Adjustment and its Relation with Learning Motivation among Fourth Year Middle School Students. ( Case study: Mohamed Sedik Ben Yahia Middle School) - amroune, salim (Journal of Social Sciences and Humanities, 2019)
The study aimed at identifying the relationship between the psychological adjustment and learning motivation for fourth year students in the city of M’sila for the academic year 2016-2017. The Sample of the study consisted of 47 students (males and females) . They were selected in a simple random way from the total number of 223 pupils who study at Mohamed Sedik Ben yahia Middle school, and based on the following hypotheses: -The level of psychological adjustment among fourth year students is high- There was a statistically significant relationship between psychological adjustment and motivation of learning among fourth year middle school students. -There were statistically significant differences between females and males in psychological adjustment among fourth year middle school students. The study was based on the descriptive method to study the variables, and for the purposes of data collection, two questionnaires were constructed, comprising (30 words), with three alternatives: (agree - I do not know - disagree) for both the psychological adjustment variable and the learning motivation variable. To verify the validity and reliability of the questionnaires, the spss-18 program was used. Using a range of statistical methods like: percentages, averages, standard deviations, order, Pearson correlation coefficient, and T-test. The results of the study are as follows: - Psychological adjustment level for fourth year students is average. - There is a statistically significant relationship between the psychological adjustment and learning motivation among fourth year middle school students. -There are no statistically significant differences between the females and males in the total psychological adjustment among fourth year middle school students. Theresults were explained in light of the theoretical framework and previous studies. Also, the researchers have recommended a number of proposals, the most important of which are: a. The need to pay attention to psychological adjustment in the school environment for its importance and its impact on the educational output, and on the achievement of students, through good treatment based on respect and mutual trust. B. Paying Attention to the educational environment and improve it because of its positive role in raising the psychological adjustment of students, and between members of the educational institution, then the general psychological atmosphere is set for the benefit of educational performance. C. It should be understood that the psychological adjustment in the school environment is not just words of courtesy to others, but additionally it is an understanding of the abilities and circumstances of the students, their motivations, their needs, respect their views and suggestions, and involve them in decisions taken within educational institutions.D. Extend communication and trust between the administrative and educational teams in the educational institutions so as to ensure the exploitation of time and management properly, and create a calm scientific atmosphere, away from the mechanical view, and neglect of humanitarian requirements.